Answer:
remainder = 122
Step-by-step explanation:
Using the remainder theorem to evaluate the remainder
Division by x - 3 , thus evaluate f(3) for remainder
f(3) = 3³ + 14(3)² - 7(3) - 10
= 27 + 126 - 21 - 10
= 122 ← remainder
Answer:
Yeah you are correct
Step-by-step explanation:
4x - 5(x - 2) = 12x + 4 - x
4x - 5(x) - 5(-2) = 12 - x + 4
4x - 5x + 10 = 11x + 4
-x + 10 = 11x + 4
<u>+ x + x </u>
10 = 12x + 4
<u>- 4 - 4</u>
<u>6</u> = <u>12x</u>
12 12
0.5 = x
Answer:
x = -2
Step-by-step explanation:
2x = -8+4
2x = -4
x = -2
CHECK
-4 - 4 = -8
Answer:
2 1/2
Step-by-step explanation:
6/4=3/2=1 1/2